Population structure of 3907 worldwide pigs and the introgression of Chinese indigenous pigs by European pigs. (23rd June 2022) - Tang, Hongbo; Ouyang, Jing; Liu, Siyu; Xiong, Yanpeng; Wu, Yongfei; Wang, Luping; Wang, Cong; Yan, Xueming; Shen, Yangyang; Chen, Hao
Abstract: With the improvement in sequencing technology and the decrease in sequencing cost, increasing amounts of genomic data for pigs have been uploaded to public databases. However, no researchers have to date integrated all currently available data to uncover the global genetic status of pigs. Meanwhile, little is known about the introgression from European to Chinese pigs and its underlying influences. Therefore, we integrated the effective genotype data of 3907 pigs from 193 populations worldwide using population genetic analysis, gene flow analysis and a sharing‐IBD study. These findings illustrate not only the population structure of 59 Chinese native breeds and others but also the amounts of gene flow and introgression that have occurred between Western and Chinese pigs. In addition, we demonstrate the presence of introgressed European haplotypes in Chinese indigenous breeds and identify relevant introgressed regions that contain genes associated with growth and feed efficiency. Moreover, we compare the introgression patterns of Western and Chinese pigs and further discuss possible explanations for why the level of introgression differs between Chinese pig breeds and Western modern breeds. Collectively, this study provides a fine global population structure analysis of pigs and presents evidence of European pigs being interbred with local breeds in China.